Users Behavior in Location-Aware Services: Digital Natives versus Digital Immigrants. (19th March 2014) - Furini, Marco
Abstract : Location-aware services may expose users to privacy risks as they usually attach user's location to the generated contents. Different studies have focused on privacy in location-aware services, but the results are often conflicting. Our hypothesis is that users are not fully aware of the features of the location-aware scenario and this lack of knowledge affects the results. Hence, in this paper we present a different approach: the analysis is conducted on two different groups of users (digital natives and digital immigrants) and is divided into two steps: (i) understanding users' knowledge of a location-aware scenario and (ii) investigating users' opinion toward location-aware services after showing them an example of an effective location-aware service able to extract personal and sensitive information from contents publicly available in social media platforms. The analysis reveals that there is relation between users' knowledge and users' concerns toward privacy in location-aware services and also reveals that digital natives are more interested in the location-aware scenario than digital immigrants. The analysis also discloses that users' concerns toward these services may be ameliorated if these services ask for users' authorization and provide benefits to users. Other interesting findings allow us to draw guidelines that might be helpful in developing effective location-aware services.